Personality, Leadership Style and Organizational Culture on Employee Performance: The Role of Work Involvement as a Mediating Variable - Angga Wira Setiawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2023)
The objects in this study were employees who worked at the Regional Inspectorate and DPMD of Kerinci Regency. The type of research used in this research is quantitative research, the data collection method is through questionnaires.The analysis technique used is multiple linear regression analysis with the help of the SmartPLS 3.0 program.The sampling technique in this study used a saturated sample by analyzing 95 respondents. Based on the results of the analysis, it can be concluded that personality has a significant effect on work involvement. Leadership style has a significant effect on work involvement. Organizational culture has a significant effect on work involvement. Personality has a significant effect on employee performance. Leadership style has a significant effect on employee performance. Organizational culture has no significant effect on employee performance. Work involvement has no significant effect on employee performance. Work involvement does not mediate the relationship between personality and employee performance. Work involvement does not mediate the relationship between leadership style and employee performance. Work involvement does not mediate the relationship between organizational culture and employee performance.